The Application of Contextual Teaching Learning Using React in Speaking Practices For Business English Class - Elli Setiyo Wahyuni (Widya Mandala Surabaya Catholic University, 2013)
The implementation of contextual teaching and learning in speaking to the first semester student of Business Administration in Hang Tuah University aims to investigate the strategies of Contextual Teaching and Learning (CTL) and the advantages of using(REACT) as one of the CTL technique. English for business is given to the students who learn English for Specific Purposes. The target of mastering this second language acquisition is able to perform well in spoken English according to their profession. In addition, The findings revealed that the teaching speaking was successful to improve students’ pronunciation and fluency.The benefits of applying REACT: (1) engaging students in the speaking activity; (2) increasing students’ motivation to participate actively in the speaking class; (3) helping students to solve their problems; (4) providing ways for students to discuss or interact with their friends. Based on these findings, it is recommended that CTL be implemented in teaching speaking.